Musical Composition in the Context of Globalization New Perspectives on Music History in the 20th and 21st Century - Utz, Christian (Musik und Klangkultur, 2021)
Since the early transformation of European music practice and theory in the cultural centers of Asia, Latin America, and Africa around 1900, it has become necessary for music history to be conceived globally - a challenge that musicology has hardly faced yet. This book discusses the effects of cultural globalization on processes of composition and distribution of art music in the 20th and 21st century. Christian Utz provides the foundations of a global music historiography, building on new models such as transnationalism, entangled histories, and reflexive globalization. The relationship between music and broader changes in society forms the central focus and is treated as a pivotal music-historical dynamic.